Support facilities and the development of quality workforce / Dr. Leo Michael Toyad - Leo, Michael Toyad (1992)
The development of quality workforce is closely linked with economic development in that it is a necessary prerequisite not only in achieving and maintaining economic development but also in promoting sustained overall goals of development. It is also closely related to Human Resource Development (HRD) in that HRD provides the basis for its development. In the context of this paper, quality workforce will be viewed in the light of the nation's declared goal of achieving the status of a fully developed nation by the year 2020. It relates to the new demands on and the kinds and qualities of the workforce needed with the transformation of the nation from an agricultural economy to an industrialised one, an economy in which science and technology becomes an integral component of socio-economic planning.